(3CQLhRI aj JYHjQ GdeUMa hGdbQGAI aj GdefGe haj JChjd ShQ GdbQBf ef Chdg Edi BNQgs - (3XgjQ GdOjf GHi eMeO GdMSjf Hf eSYhO GdHZhi GdaQGAs; (3GdHZhj , GdMSjf Hf eSYhO Hf eMeO GdaQGA, eMjj GdSfI CHh eMeO,J (B510 (3g` s
(3ChdgG (B:s
(3hGdeUMa GdfPjQ ai GdefGe jfSH ai GdQDjG Edi GdGMcGe s
(3BNQgG (B:s
(3hNGJe GdbQBf ai GdefGe JbVi dg GdMGLGJ HGdSdGe s
(3hQO GSe GdeDda ai Chd UaMI HNW eZGjQ dNW GdfSNIs
(3JHUQI GdYfhGf (B:s
(3fXes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B259 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B61s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B12 s
Keywords: (3JYHjQ GdQDjGs